Levantamento de solos e classificação da capacidade de uso das terras no projeto de assentamento moacir lucena, Apodi-RN - Dias, Pollyana Mona Soares (2018)
Soil is one of the main natural resources used on agricultural practices; however, the process on its exploration may make it drainable, which requires determining the correct usage and management of this soil that can only be found by understanding of various attributes involved, through a physical survey. Thus, this study proposes to make a soil survey on Moacir Lucena Settlement Project in Apodi city, with its morphological and physicochemical characterization, along with the capacity classification of land use comparing to the current use. The Moacir Lucena Settlement Project is situated in Chapada do Apodi,RN, and it was subdivided in seven representative areas for this study: Profile 1 (IBAMA recovering area), Profile 2 (Pond area), Profile 3 (Permanent preservation area or IBAMA area), Profile 4 (Agroecological management area), Profile 5 (Collective planting area), Profile 6 (Cashew tree collective area) and Profile 7 (Cashew tree collective area 2). Deformed and non-deformed soil samples were collected on the horizon of those profiles and were made physical analysis (granulometry, clay dispersed in water, silt/clay ratio, soil density, particle density, total porosity, flocculation degree), chemical analysis (pH, electrical conductivity, total organic carbon, Ca+2, Mg+2, K+, Na+, P, Al3+, sum of bases, cation exchange capacity, bases saturation percentage, saturation by aluminum, total sodium percentage), infiltration test with ring infiltrometer, soil mechanical resistance to penetration and classification of land use capacity. The results were analyzed by submitting them to the multivariate statistical techniques, by means of correlation matrix, cluster analysis and factor analysis with the factor extraction in the main components. The soils were classified as follows: Profile 1 (RED-YELLOW LATOSOL Argisolic Eutrophic); Profile 2 (HAPLIC CAMBISOL Typical carbonate); Profile 3 (YELLOW LATOSOL Argisolic Eutrophic); Profile 4 (YELLOW ARGISOL Typical Eutrophic); Profile 5 (HAPLIC CAMBISOL Tb Typical Eutrophic); Profile 6 (YELLOW LATOSOL Argisolic Eutrophic) and Profile 7 (YELLOW LATOSOL Argisolic Eutrophic). In general, the soils are poorly weathered, with physical limits regarding the effective depth and soil mechanic resistance to penetration. The Basic Infiltration Rate calculated has varied as medium to the Argisol (Profile 4), high to Latosol (Profile 1), very high to the other profiles (Cambisol (Profile 2), Cambisol (Profile 5), Latosol (Profiles 7, 3 and 6). A variation has occurred on the soil mechanical resistance to penetration, between 1332 and 6769 kPa, and its classification from low to very high, showing variability to different depths, soil classes and use. The settlement presents use intensity considered as under capacity, the area in recovering belongs to the Group B, improper lands for intense cultivation, but yet adapted to reforestation and wildlife, and Class VI, adapted lands in the settlement, reforestation area for preservation with simple problems of conservation and only cultivable in special cases of permanent protective cultures of soil, the Pond area in Group C, which are not suitable lands for annual cultivation, perennial, pasture and reforestation, however they are suitable for fauna and flora protection, recreation or water storage, mainly in rainy season, and Class VIII, are not suitable for culture, pasture or reforestation, that can be used only as shelter and fauna and flora protection, as a recreation environment or water storage purpose, the collective use area and cashew tree areas belonging to Group A, with can be used for annual cultures, perennial, pasture, and/or reforestation and wildlife, and Class II, cultivable lands, with simple problems of conservation and/or improvement maintenance. However, as Permanent Preservation Area, IBAMA areas, Pond area and Permanent Preservation in recovering cannot be economically explored